MODELLING OF ACCOUNTING AND ORGANIZATIONAL, SOCIAL AND ENVIRONMENTAL PROCESSES IN RESIDENTIAL CONSTRUCTION (INNOVATIVE ECONOMY, 2026)
Gumenna-Derii M.V. MODELLING OF ACCOUNTING AND ORGANIZATIONAL, SOCIAL AND ENVIRONMENTAL PROCESSES IN RESIDENTIAL CONSTRUCTIONPurpose. The aim of this article is to develop a model of organizational and economic, social and environmental processes in residential construction.Methodology of research. General scientific and specific research methods were applied in modelling accounting and organizational, social and economic processes in residential construction. The monographic method made it possible to evaluate the scientific achievements of researchers in this field. Analysis of data on capital investments across the regions of Ukraine determined the impact of the war on the level of capital investments in regions where hostilities are taking place. The modelling method contributed to the development of a model of accounting and organizational, social and economic processes in residential construction. The comparative method enabled the identification of software solutions worldwide according to the size of construction enterprises (small, medium, and large). Findings. The role and significance of accounting and organizational, social and economic processes in residential construction were highlighted; their identification makes it possible to determine the advantages and disadvantages of this sector. It has been substantiated that the model of accounting and organizational, social and economic processes in residential construction allows for the identification of problematic aspects in the development of financial and management accounting, as well as financial, managerial, and social reporting, with the aim of ensuring prompt and effective managerial decision-making. Proposals were provided for improving the economic and environmental aspects of residential construction, socially oriented programs, internal control, and digitalization, while ensuring compliance with the regulatory and legal framework.Originality. Models of accounting, organizational, social and economic processes in housing construction have been developed, which, in addition to existing ones, provide an opportunity to comprehensively assess the processes that occur in construction during management. Measures are proposed for assessing and forming problematic aspects of construction enterprises, forming a high-quality accounting policy, minimizing risks, choosing the optimal software product and making high-quality management decisions.Practical value.  The provided proposals can be used by enterprises, government authorities, and territorial communities to assess the operational status of construction companies. They contribute to improving accounting policy and the strategic development of construction enterprises, and facilitate effective managerial decision-making.Key words: accounting and organizational processes, social and environmental processes, residential construction.
Keywords: accounting and organizational processes; social and environmental processes; residential construction